'Nacimos de la nada': border struggles and maternal politics in Mexico. Issue 5 (3rd July 2016) - Kron, Stefanie
Abstract: Since 2006, at least 70, 000 transit migrants from Central America have gone 'missing' in Mexico. This has led to political mobilizations of pro-migrant groups throughout Central America and Mexico. Within this movement for migrants' rights, motherist groups like the 'Caravan of Central American mothers' of missing migrants stand out. These groups demand rights to know what happened with their missing relatives. I argue that motherist groups are mobilizing motherhood 'as a site of political agency.' This paper analyses the actors, strategies, and practices of the 'Caravan of Central American mothers, ' a yearly public march through Mexico, by using a non-formal and feminist concept of citizenship as well as the idea of 'maternal politics.' I do so in order to show that within the current border struggles, motherhood may turn into a radical and political subjectivity. The analytical focus on the role that motherhood plays in migrant and pro-migrant activism may expand our awareness about the gendered nature of citizenship and ways of being political.